2016
DOI: 10.1111/anu.12428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary selenium sources (sodium selenite, selenomethionine and nanoselenium) on growth performance, muscle composition, blood enzymes and antioxidant status of common carp (Cyprinus carpio)

Abstract: This experiment was conducted to compare the effects of different sources of selenium (Se) on growth, muscle Se concentration, muscle proximate composition, blood enzymes and antioxidant status of common carp, Cyprinus carpio. Organic Se (selenomethionine, SeMet), inorganic Se (sodium selenite, Na2SeO3), or nanoselenium were each added to the basal diet at 0.7 mg Se kg−1 diet. Four groups of fish with an average weight of 9.69 ± 0.12 g were fed one of the experimental diets for 8 weeks. Nano‐Se diet resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 36 publications
11
68
1
Order By: Relevance
“…Se as an essential nutrient for fish has been researched in many fish species, including grass carp (Liu et al, , ; Saffari, Keyvanshokooh, Zakeri, Johari, & Pasha‐Zanoosi, ; Xia et al, ; Zhou, Wang, Gu, & Li, ). Se nanoparticle (Nano‐Se) is the novel Se form and has attracted remarkable attention, as it exhibits higher bioavailability, lower toxicity and strong bioactivity in comparison with inorganic and organic Se (Saffari et al, , ; Zhou et al, ). Zhou et al () showed that Nano‐Se are more efficient in increasing muscle Se content compared to organic Se (selenomethionine, SeMet) in the crucian carp (Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Se as an essential nutrient for fish has been researched in many fish species, including grass carp (Liu et al, , ; Saffari, Keyvanshokooh, Zakeri, Johari, & Pasha‐Zanoosi, ; Xia et al, ; Zhou, Wang, Gu, & Li, ). Se nanoparticle (Nano‐Se) is the novel Se form and has attracted remarkable attention, as it exhibits higher bioavailability, lower toxicity and strong bioactivity in comparison with inorganic and organic Se (Saffari et al, , ; Zhou et al, ). Zhou et al () showed that Nano‐Se are more efficient in increasing muscle Se content compared to organic Se (selenomethionine, SeMet) in the crucian carp (Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al () showed that Nano‐Se are more efficient in increasing muscle Se content compared to organic Se (selenomethionine, SeMet) in the crucian carp (Zhou et al, ). Saffari et al () showed that Nano‐Se acts more efficiently on growth performance and antioxidant defence system of common carp than the organic and inorganic sources of Se. Ashouri, Keyvanshokooh, Salati, Johari, and Pasha‐Zanoosi () showed that supplementation of Se nanoparticles could improve growth performance and antioxidant defence system of common carp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, hepatopancreatic MDA content did not decrease at Se level of 0.57 mg/kg, while which owns the highest hepatopancreatic and serum GPx activity. In previous studies, MDA was negatively correlated with increasing GPx activity in common carp and gibel carp with Se supplement (Liu et al, ; Saffari, Keyvanshokooh, Zakeri, Johari, & Pasha‐Zanoosi, ). The increased hepatopancreatic SOD at dietary Se levels of 0.79 and 1.00 mg/kg may compensate for the lack of greater expression of GPx in this study, as SOD was reported to combat oxidative stress in conjunction with GPx in the antioxidant systems (Zee, Patterson, Wiseman, & Hecker, ).…”
Section: Discussionmentioning
confidence: 80%